Effect of Implant Positions and Angulations on Retentive Strength of 2-Implant Mandibular Overdentures: An In Vitro Study with the New 3D-Printed Simulation Method. (14th September 2022) - Patil, Pravinkumar G.; Seow, Liang Lin; Uddanwadikar, Rashmi; Pau, Allan; Ukey, Piyush D.
Abstract : Objectives . To evaluate the retentive strength of overdenture attachments in 2-implant mandibular overdenture (2IMO) with implants placed at different positions and angulations. Materials and Methods . Edentulous mandibular models were 3D-printed using CBCT images and Materialise Mimics software and the denture models using the intraoral scanner. Two standard implants were placed parallel at different positions from midline (5, 10, 15, and 20 mm) with 0-0 degree angulations and with different distal angulations (0–5, 0–10, 0–15, 5-5, 10-10, and 15-15 degrees) at 10±mm from midline representing 10 study groups. Low-profile male attachments were attached to the implants and the female pink attachments were picked up in the denture. A total of 4 simulated overdenture model sets for each of the 10 study groups were subjected to the universal testing machine thrice to measure a peak load (N) to disengage the attachments vertically. Data were analyzed using one-way ANOVA and Tukey's post hoc test at 0.05 significance level. Results . Varying implant positions had a statistically significant effect on the retentive strengths of the attachments ( F  = 5.61, P = 0.002 ). Peak load-to-dislodgement values (in increasing order) were 49.64 ± 8.27 N for 5 mm, 53.26 ± 11.48 N for 10 mm, 60.24 ± 12.31 N for 15 mm, and 64.80 ± 6.78 N for 20 mm groups. The retentive strength of the 20 mm group was significantly higher than 5 mm (P = 0.003 ) and 10 mm (P = 0.03 ) groups. Varying implant angulations had a significant effect on the retentive strengths of the attachments ( F  = 7.412, P = 0.000 ). The peak load-to-dislodgement values (in increasing order) were 48.20 ± 15.59 N for 5-5 degrees, 53.26 ± 11.48 N for 0-0 degrees, 54.96 ± 8.25 N for 0–5 degrees, 57.71 ± 7.62 N for 10-10 degrees, 66.00 ± 17.54 N for 15-15 degrees, 66.18 ± 14.09 N for 0–10 degrees, and 77.38 ± 10.33 N for 0–15 degrees. Retentive strength of 0–15 degrees was significantly (P < 0.05 ) higher than those of 0-0, 0–5, 5-5, and 10-10 degrees and that of 5-5 degrees was significantly (P < 0.05 ) lower than those of 0–10, 0–15, and 15-15 groups. Conclusions . Retentive strength of the 2IMO increased with increase in distance of implants from midline and increased with increase in distal angulations.